Interference Reduction Using Principles and Application of Cognitive Radar in Pulse Jammer Suppression - Bestak, Robert (IRO Journal on Sustainable Wireless Systems, 2020)
The increase in the number of emitters operating at a frequency close to that of the modern radar systems impose a major challenge on the rapidly developing market for communication systems and the increasing demand for electromagnetic spectrum. Interference problems occur when multiple radar systems of the same type operate in the same environment with limited bandwidth availability and leads to frequency regions overlap. The radar systems incur significant performance losses due to the inferences caused under such circumstances. The concept of Cognitive Radar can provide solutions for such issues. This paper provides an improved Cognitive Radar architecture to address these challenges. The strong interference signals are suppressed using adaptive processing technique. The significant market advantages and application overview of this system is also presented in this paper.